Perlindungan Hukum Anak Korban Perkosaan Inses dalam Sistem Peradilan Pidana - Sudarti, Elly; Usman, Usman; Arfa, Nys. (Universitas Batanghari Jambi, 2024)
This article discusses the legal issue of protecting the rights of children who are victims of incest rape after abortion in the law enforcement process. The crimes that occur should be resolved by the criminal justice system. In fact, child victims of incest rape have not received protection at every stage of the examination, from the investigation, prosecution to court decision. The importance of protecting child victims can be seen as a form of protection by the state in the form of administering justice. Apart from the completeness of statutory regulations regarding the protection of child victims, (the Witness and Victim Protection Agency), law enforcement officials, related government agencies and other relevant parties, the function of the judiciary plays an important role. This article aims first, to analyze the regulations regarding forms of protection for victims of incest rape in the criminal justice system. Second, it aims to analyze the enforcement of legal protection for child victims of incest rape in the judicial system. The method used in this article is a normative juridical research type using a statutory approach, conceptual approach and case approach. Analysis of legal materials, namely legal materials and literature that have been collected through systematic methods and then analyzed by inventorying, systematizing and interpreting all legal regulations and concepts according to the problems discussed. Substantially, from a regulatory perspective, a lot has been regulated regarding legal protection for child victims of incest, but in law enforcement it has not been able to provide protection, because the regulations for victim protection are still partially regulated. Studies of court decisions have not been able to accommodate the values of legal efficacy and the value of legal justice in providing legal protection to child victims of incest rape, especially in the criminal justice system. This study is important to carry out so that in the future there will be legal harmonization regarding legal protection for child victims of incest in the future.